THE SCOTIST LOGIC OF JERÓNIMO VALERA O.F.M. (1568–1625): LOGIC OF CATEGORIES OR TRANSCENDENTAL LOGIC? - Hofmeister Pich, Roberto (Thaumazein: Revista Online de Filosofia, 2016)
<!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> In this study, I make the attempt of illustrating two aspects on which Jerónimo Valera O.F.M. (1568–1625) introduces, inside his Commentarii ac quaestiones in universam Aristotelis ac Subtilissimi Doctoris Ioannis Duns Scoti logicam (1610), logical-metaphysical themes that extrapolate the explicit contents of Scotus’s works about logic. I have in view both the concepts of “infinite being” and “infinity” and a given account of categorial quantity and its properties. The focus of textual analysis are some Questions of the Liber Secundus in quo praedicamenta Aristotelis Stagiritae expenduntur, i.e. the third and last part of the volume written by Jerónimo Valera. For the first aspect, Valera reveal a fine capacity of distinguishing kinds of infinity and the ways how categorial logic and transcendental logic must consider such a notion. Moreover, his view on categorial quantity depends on his assumption of the mystery of the eucharisty, what led him to emphasize and rationally defend the conceivability of some particular and fundamental properties of extensive quantity. <!--EndFragment-->